Wacana kebudayaan: Pandangan dari berbagai pakar - Sagita, Diva Aulia; Ghozi, Ahmad; Fransiska, Ayu; Basmallah, Aisy Aulia (Maliki Interdisciplinary Journal, 2024)
This journal examines the views of several cultural experts regarding culture in general, with the aim of understanding the meaning, theory, and dynamics of culture in a comprehensive manner. As a complex concept, culture includes various aspects including language, customs, values, and beliefs, which indirectly form an identity within an individual or group. Through in-depth analysis, this journal explores various cultural theories, including the contributions of experts to the development of the theory. Apart from that, it also includes culture in various contexts. Such as in the context of globalization and technology, it is also discussed to understand how cultures adapts to the times. The role of education and economics in preserving and spreading culture is also studied by providing examples in the form of relevant case studies. Criticism and controversy in cultural analysis do not go unnoticed, so that it is able to provide a balanced perspective and view. This journal concludes that the views of various experts regarding cultures provide valuable insights in understanding culture as a continually developing phenomenon.